Comparative study on transient response analysis of hybrid laminated composite plates with experimental verification. (4th August 2019) - Biswas, Dhiraj; Ray, Chaitali
Abstract: This paper attempts in analysing the transient dynamic response behaviour of multi layered hybrid composite plates by a modified higher order refined zigzag theory (HRZT). An improved C 0 continuous model is developed based on the refined higher order zigzag theories (HRZT) with warping effect for multilayered plates using eight noded isoparametric quadratic plate bending element to get the stress distribution across the thickness under dynamic load in a realistic manner. The continuity condition of transverse shear stresses is ensured with the help of 3D equilibrium equation at the interfaces of two adjacent layers along with the shear stress free condition at the outermost faces of a laminate. A computer code is developed with the help of MATLAB software package. The hybrid laminate is modeled by placing carbon fibres in the outermost layers and glass fibres in the rest and thus the flexural behaviour is improved. The experimental study on the transient dynamic response of hybrid laminates is also performed. Transient dynamic response obtained from the finite element based numerical model is verified by comparing the time history data obtained numerically and experimentally. The interlaminar stresses are also extracted and recorded under dynamic loading condition. The displacement and the stress components of laminated plates under static load are also computed in the present study and the results are compared with the theoretical outcome obtained in the relevant literature for validation of the present FE formulation. An exhaustive study on glass and hybrid fibre reinforced laminates is carried out to investigate the effectiveness of the hybrid laminate in terms of the response data of laminates with mono fibre as well as multiple (hybrid) fibres.